2011
DOI: 10.1016/j.ijgo.2010.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Specific exercises to treat pregnancy‐related low back pain in a South African population

Abstract: A specific exercise program decreased back pain intensity and increased functional ability during pregnancy in South African women with lumbar and pelvic girdle pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 28 publications
1
74
1
3
Order By: Relevance
“…As to the exercises that were supervised by different therapists, previous studies found that these strategies were efficient for pregnancy low back and pelvic pain (8)(9)(10). The importance of supervision during the exercises for the treatment and prevention of low back pain is also emphasized in studies that did not focus solely on pregnant women (45,46).…”
Section: Group and Individual Protocols With Or Without Supervisionmentioning
confidence: 99%
See 3 more Smart Citations
“…As to the exercises that were supervised by different therapists, previous studies found that these strategies were efficient for pregnancy low back and pelvic pain (8)(9)(10). The importance of supervision during the exercises for the treatment and prevention of low back pain is also emphasized in studies that did not focus solely on pregnant women (45,46).…”
Section: Group and Individual Protocols With Or Without Supervisionmentioning
confidence: 99%
“…The fact that there is no consensus about the duration and frequency of the interventions was also found by other studies that assessed the effects of the exercises on pregnant women. The studies by Elden et al (8) and Kordi et al (11) showed that exercises performed during six weeks reduced pelvic pain, and according to Kluge et al (10) an exercise program that lasted 10 weeks reduced the intensity of pregnancy low back pain and increased the functional capacity of the participants. The studies by Garashabi et al (9) and Schim et al (26) found a reduction in the intensity of low back and conflicting evidence, because they differed as to the duration of the interventions, the effects on pain intensity and on functional limitations; on the study that found positive results (37), the duration of the intervention was only a week.…”
Section: Duration and Frequency Of The Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The beneficial effect can be still visible as long as two years later [17,18]. Some authors reported a positive effect of stabilizing exercises as early as in the pregnancy period [16,19,20]. There is limited evidence, however, on the specificity of the training and exercises that should be done, since only a few studies investigated the impact of a particular type of movement activity [21].…”
Section: Fizjoterapiamentioning
confidence: 99%